(untitled) (Scientific journal of the Fergana State University, 2023)
This article is focused on the questions of scientific study of such paremiological genres of folklore as proverbs, parabolas, spells, lessings, winged words, gregorie, paradox, curse, prayers, beliefs and eloquences which possessa a special place in oral folk creativeness even centuries later